Representações da dor da perda em Chico Buarque: Uma leitura de pedaço de mim, Angélica e meu guri. - Ribeiro, Ligia Maria Ramalho (2018)
In this work, we propose a reflection on the issue of loss pain, whether symbolic, because what is lost is not a being, but power, prestige, control of a situation, that is, a loss of one's own ego, the loss of one who is loved and, above all, the loss we consider the greatest of them all, the pain of the mother who had the life of a son harvested. In this course, we will analyze, through songs by Chico Buarque de Hollanda, in the light of Sigmund Freud, psychoanalysis, as well as through the teacher and psychoanalyst J. D-Nasio, how the loss invades and devastates the life of those who are affected by it . We will take a closer look at feelings of love, pain and death. In the context of our reflection, they are feelings that are intertwined and permeate all the way that we will travel from the reflections that the songs Piece of Me, Angelica and My Guri, in a poetic and deep way that these songs allow us to enter the universe of loss for someone or something you love.